1988
DOI: 10.1677/joe.0.1180429
|View full text |Cite
|
Sign up to set email alerts
|

Tumour formation and insulin secretion by clonal RINm5F cells following repeated subcutaneous transplantation in NEDH rats

Abstract: The effects of repeated s.c. transplantation of clonal insulin-secreting RINm5F cells in NEDH rats on tumour morphology, insulin-glucose homeostasis and the function of RINm5F cells re-established in culture were examined after maintenance in vivo for periods of up to 308 days. Transplantation of RINm5F cells for ten consecutive passages consistently produced a single encapsulated vascularized tumour associated with the development in recipient rats of hyperinsulinaemia, hypoglycaemia and eventual neuroglycope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The glucose responsiveness exhibited by the BRIN-BD11 cell line indicates that these cells do not suffer from the inherent defect recorded with parental RINm5F cells (21,22,50,51). Collectively these studies demonstrate that BRIN-BD11 cells have inherited many key attributes of the normal pancreatic (B-cell and that they represent a particularly useful cell line for future research into pancreatic p-cell function.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The glucose responsiveness exhibited by the BRIN-BD11 cell line indicates that these cells do not suffer from the inherent defect recorded with parental RINm5F cells (21,22,50,51). Collectively these studies demonstrate that BRIN-BD11 cells have inherited many key attributes of the normal pancreatic (B-cell and that they represent a particularly useful cell line for future research into pancreatic p-cell function.…”
Section: Discussionmentioning
confidence: 75%
“…The characteristics of parental RINm5F cells used for electrofusion have been described by the authors in detail elsewhere (21,22). These cells exhibit a low insulin content and basal insulin release, together with glucose unresponsiveness or even inhibition of insulin secretion in acute incubations.…”
mentioning
confidence: 99%
“…their cellular insulin content compared with only 9% from BRIN-BG7 cells. Both cells had basal levels of insulin secretion substantially higher than the very modest output characteristic of the parental RINm5F cell (Flatt et al , 1988.…”
Section: Discussionmentioning
confidence: 87%
“…Cells were gently washed in 10 ml Hank's balanced salt solution (HBSS) prior to detachment from the culture flasks by incubation with 0-025% (w/v) trypsin/EDTA (Gibco) and immediately utilized. The RINm5F cells used in these electrofusion studies have been extensively characterized elsewhere (Flatt et al , 1988. These cells have been noted to have a low basal insulin release, coupled with a glucose unresponsiveness or even inhibition of insulin secretion in acute incubations with increasing glucose concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The radiation-induced insulin secreting RINm5FceIl line has been used in several studies on cytoioxicity to beta cells (Flatter at.. 1987), Tcell specificity for beta cells (Prud'homme cr ai, 1986;van Vliet et at.. 1989) and beta cell specificity in transplantation (Flatt et at.. 1988). In these studies it was demonstrated that RINm5F cells express antigens relevant for autoimmune cell-mediated reactivity in type !…”
Section: Introductionmentioning
confidence: 99%